Influence of thermo-mechanical joining process on the microstructure of a hypoeutectic aluminium cast alloy - Borgert, Thomas; Neuser, Moritz; Wiens, Eugen; Grydin, Olexandr; Homberg, Werner; Schaper, Mirko (Materials Research Proceedings)
Requirements of multi-material construction involve adjustments to standard joining techniques. Especially the growing importance of integral cast components poses additional engineering challenges for the industry. One approach to achieve these goals are adaptable joining elements formed by friction spinning. This approach uses friction-induced heat to form customisable joining elements to join sheets for different boundary conditions, even for brittle cast materials. It is possible to react immediately to adapt to the joining process inline and reduce the amount of different joining elements. As the joining partner serve casting plates of the aluminium casting alloy EN AC–AlSi9, which is processed in the sand casting. Joining hypoeutectic AlSi alloys constitutes a challenge because the brittle character of these cause cracks in the joint during conventional mechanical joining. Furthermore, the friction-induced heat of the novel joining process causes a finer microstructure in the hypoeutectic AlSi9 casting alloy. In particular, the eutectic Si is more fine-grained, resulting in higher joint ductility. This study indicates the joining suitability of a hypoeutectic aluminium casting alloy in combination with adaptive manufactured additional joining elements. Here, various mechanical and microstructural investigations validate the influence of the thermomechanical joining technique. In conclusion, the potential of this joining process is presented regarding the joinability of cast aluminium components.

Mechanical and Microstructure Characterisation of the Hypoeutectic Cast Aluminium Alloy AlSi10Mg Manufactured by the Twin-Roll Casting Process - Neuser, Moritz; Schaper, Mirko; Grydin, Olexandr (Journal of Manufacturing and Materials Processing)
Multi-material designs (MMD) are more frequently used in the automotive industry. Hereby, the combination of different materials, metal sheets, or cast components, is mechanically joined, often by forming joining processes. The cast components mostly used are high-strength, age-hardenable aluminium alloys of the Al–Si system. Here, the low ductility of the AlSi alloys constitutes a challenge because their brittle nature causes cracks during the joining process. However, by using suitable solidification conditions, it is possible to achieve a microstructure with improved mechanical and joining properties. For this study, we used the twin-roll casting process (TRC) with water-cooled rollers to manufacture the hypoeutectic AlSi10Mg for the first time. Hereby, high solidification rates are realisable, which introduces a microstructure that is about four times finer than in the sand casting process. In particular, it is shown that a fine microstructure close to the modification with Na or Sr is achieved by the high solidification rate in the TRC process without using these elements. Based on this, the mechanical properties increase, and especially the ductility is enhanced. Subsequent joining investigations validate the positive influence of a high solidification rate since cracks in joints can be avoided. Finally, a microstructure-property-joint suitability correlation is presented.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Influence of Shell Material on the Microstructure and Mechanical Properties of Twin-Roll Cast Al-Si-Mg Alloy - Grydin, Olexandr; Neuser, Moritz; Schaper, Mirko (Conference: ICTP 2023: Proceedings of the 14th International Conference on the Technology of Plasticity - Current Trends in the Technology of PlasticityAt: Cannes (France))

Experimental and Numerical Investigation of Clinched Joints Under Shear Tensile Loading at High Strain Rates - Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Lecture Notes in Mechanical Engineering)

Mechanical Properties and Joinability of AlSi9 Alloy Manufactured by Twin‐Roll Casting - Neuser, Moritz; Kappe, Fabian; Ostermeier, Jakob; Krüger, Jan Tobias; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko; Grydin, Olexandr (Advanced Engineering Materials)
AlSi casting alloys combine excellent castability with high strength. Hence, this group of alloys is often used in the automotive sector. The challenge for this application is the brittle character of these alloys which leads to cracks during joint formation when mechanical joining technologies are used. A rise in ductility can be achieved by a considerable increase in the solidification rate which results in grain refinement. High solidification rates can be realized in twin–roll casting (TRC) by water-cooled rolls. Therefore, a hypoeutectic EN AC–AlSi9 (for European Norm - aluminum cast product) is manufactured by the TRC process and analyzed. Subsequently, joining investigations are performed on castings in as-cast and heat-treated condition using the self-piercing riveting process considering the joint formation and the load-bearing capacity. Due to the fine microstructure, the crack initiation can be avoided during joining, while maintaining the joining parameters, especially by specimens in heat treatment conditions. Furthermore, due to the extremely fine microstructure, the load-bearing capacity of the joint can be significantly increased in terms of the maximum load-bearing force and the energy absorbed.
Keywords: Condensed Matter Physics; General Materials Science

Influence of Kinematic Hardening on Clinch Joining of Dual-Phase Steel HCT590X Sheet Metal - Friedlein, Johannes; Mergheim, Julia; Steinmann, Paul (The Minerals, Metals & Materials Series)
Nowadays, clinching is a widely used joining technique, where sheets are joined by pure deformation to create an interlock without the need for auxiliary parts. This leads to advantages such as reduced joining time and manufacturing costs. On the other hand, the joint strength solely relies on directed material deformation, which renders an accurate material modelling essential to reliably predict the joint forming. The formation of the joint locally involves large plastic strains and possibly complex non-proportional loading paths, as typical of many metal forming applications. Consequently, a finite plasticity formulation is utilised incorporating a Chaboche–Rousselier kinematic hardening law to capture the Bauschinger effect. Material parameters are identified from tension–compression tests on miniature spec- imens for the dual-phase steel HCT590X. The resulting material model is implemented in LS-Dyna to study the locally diverse loading paths and give a quantitative statement on the importance of kinematic hardening for clinching. It turns out that the Bauschinger effect mainly affects the springback of the sheets and has a smaller effect on the joint forming itself.
Keywords: Clinching; Material modelling; Kinematic hardening; Parameter identification; Bauschinger effect

Numerical and experimental identification of fatigue crack initiation sites in clinched joints - Ewenz, L.; Bielak, Christian Roman; Otroshi, Mortaza; Bobbert, Mathias; Meschut, Gerson; Zimmermann, M. (Production Engineering)
In this paper, a study based on experimental and numerical simulations is performed to analyze fatigue cracks in clinched joints. An experimental investigation is conducted to determine the failure modes of clinched joints under cyclic loading at different load amplitudes with single-lap shear tests. In addition, numerical FEM simulations of clinching process and subsequent shear loading are performed to support the experimental investigations by analyzing the state of stresses at the location of failure. An attempt is made to explain the location of crack initiation in the experiments using evaluation variables such as contact shear stress and maximum principal stress.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Joining Processes for Fibre-Reinforced Thermoplastics: Phenomena and Characterisation - Troschitz, Juliane; Gröger, Benjamin; Würfel, Veit; Kupfer, Robert; Gude, Maik (Materials)
Thermoplastic composites (TPCs) are predestined for use in lightweight structures, especially for high-volume applications. In many cases, joining is a key factor for the successful application of TPCs in multi-material systems. Many joining processes for this material group are based on warm forming the joining zone. This results in a change of the local material structure characterised by modified fibre paths, as well as varying fibre contents, which significantly influences the load-bearing behaviour. During the forming process, many different phenomena occur simultaneously at different scales. In this paper, the deformation modes and flow mechanisms of TPCs during forming described in the literature are first analysed. Based on this, three different joining processes are investigated: embedding of inserts, moulding of contour joints, and hotclinching. In order to identify the phenomena occurring in each process and to describe the characteristic resulting material structure in the joining zones, micrographs as well as computed tomography (CT) analyses are performed for both individual process stages and final joining zones.

Forming process induced material structure of fibre-reinforced thermoplastics - Experimental and numerical investigation of a bladder-assisted moulding process - Gröger, B.; Würfel, V.; Hornig, A.; Gude, M. (Journal of Advanced Joining Processes)

Design of clinched joints on the basis of binding mechanisms - Kalich, J.; Füssel, U. (Production Engineering)
The work carried out is based on the thesis properties of clinched joints are determined by the proportions of binding mechanisms form-closure, force-closure and material-closure. To describe the acting binding mechanisms and thus to derive the joint properties, detailed knowledge of the local effect of the individual binding mechanisms is necessary to ensure their targeted adjustment by the joining process. The targeted setting of different proportions of the binding mechanisms is achieved firstly via tool geometry and secondly via surface condition of the joined parts. An introduced form-closure component can be quantified by metallographic cross section with subsequent measurement of the quality-determining parameters such as undercut, penetration depth and neck thickness. To qualify the force-closure component, a torsional load can be applied mechanically at rotationally symmetrical clinch joints. This also allows the influence of different surface conditions on the tribological system to be quantified. Measurement of electrical resistance can reveal the binding mechanisms of force- and material-closure. These investigations are carried out on an aluminum joining part combination of the same type. As a result of these investigations, the clinched joints can be designed according to the load occurring in the later life cycle in the form of an optimum and compromise variant with regard to minimum loads to be transmitted mechanically, electrically with regard to low resistance or manufacturing with minimum energy input.

Observations on additive plasticity in the logarithmic strain space at excessive strains - Friedlein, J.; Mergheim, J.; Steinmann, P. (International Journal of Solids and Structures)
Additive plasticity in the logarithmic strain space is compared to multiplicative plasticity for various loading cases including coaxial and non-coaxial plastic deformations. Even though both finite plasticity approaches are based on total Lagrangian descriptions, the former is popular due to its inherent similarity to the infinitesimal theory and its easy extensibility. However, since its introduction several limitations of additive plasticity in the logarithmic strain space have been discovered. In this study, these problems such as stress rotation and softening are considered, revealing that fundamental differences compared to multiplicative plasticity occur for non-coaxial plastic deformations. We focus in particular on the observed softer response of the additive based approach, which is analysed in depth using three numerical examples including two well-known benchmarks for finite plasticity. By means of these finite element simulations the softer and possibly even localising response of additive plasticity in the logarithmic strain space is confirmed.

The Influence of Heat Treatment on the Microstructure, Surface Roughness and Shear Tensile Strength of AISI 304 Clinch Joints - Zeuner, André Till; Ewenz, Lars; Kalich, Jan; Schöne, Sebastian; Füssel, Uwe; Zimmermann, Martina (Metals)
Clinching is the manufacturing process of joining two or more metal sheets under high plastic deformation by form and force closure without thermal support and auxiliary parts. Clinch connections are applicable to difficult-to-join hybrid material combinations, such as steel and aluminum. Therefore, this technology is interesting for the application of AISI 304 components, as this material is widely used as a highly formable sheet material. A characteristic feature of AISI 304 is its metastability, i.e., the face-centered cubic (fcc) γ-austenite can transform into a significantly stronger body-centered cubic (bcc) α’-martensite under plastic deformation. This work investigates the effect of heat treatment—a process that involves the formation of an oxidation layer on the sheet surface—on the forming process during joining and the resulting mechanical properties of clinch joints made from AISI 304. For this purpose, different joints made from non-heat treated and heat-treated sheets were examined using classical metallography and advanced SEM techniques, accompanied by further investigations, such as hardness and feritscope measurements. The shear tensile strength was determined, and the fracture behavior of the samples was investigated. Clear influences of heat-treatment-induced surface roughness on the joint geometry and strength were observed.
Keywords: General Materials Science; Metals and Alloys

Characterisation of Fibre Bundle Deformation Behaviour—Test Rig, Results and Conclusions - Borowski, Andreas; Gröger, Benjamin; Füßel, René; Gude, Maik (Journal of Manufacturing and Materials Processing)
Deformation of continuous fibre reinforced plastics during thermally-assisted forming or joining processes leads to a change of the initial material structure. The load behaviour of composite parts strongly depends on the resultant material structure. The prediction of this material structure is a challenging task and requires a deep knowledge of the material behaviour above melting temperature and the occurring complex forming phenomena. Through this knowledge, the optimisation of manufacturing parameters for a more efficient and reproducible process can be enabled and are in the focus of many investigations. In the present paper, a simplified pultrusion test rig is developed and presented to investigate the deformation behaviour of a thermoplastic semi-finished fiber product in a forming element. Therefore, different process parameters, like forming element temperature, pulling velocity as well as the forming element geometry, are varied. The deformation behaviour in the forming zone of the thermoplastic preimpregnated continuous glass fibre-reinforced material is investigated by computed tomography and the resultant pulling forces are measured. The results clearly show the correlation between the forming element temperature and the resulting forces due to a change in the viscosity of the thermoplastic matrix and the resulting fiber matrix interaction. In addition, the evaluation of the measurement data shows which forming forces are required to change the shape of the thermoplastic unidirectional material with a rectangular cross-section to a round one.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Warmforming Flow Pressing Characteristics of Continuous Fibre Reinforced Thermoplastic Composites - Gröger, Benjamin; Römisch, David; Kraus, Martin; Troschitz, Juliane; Füßel, René; Merklein, Marion; Gude, Maik (Polymers)
The paper presents research regarding a thermally supported multi-material clinching process (hotclinching) for metal and thermoplastic composite (TPC) sheets: an experimental approach to investigate the flow pressing phenomena during joining. Therefore, an experimental setup is developed to compress the TPC-specimens in out-of-plane direction with different initial TPC thicknesses and varying temperature levels. The deformed specimens are analyzed with computed tomography to investigate the resultant inner material structure at different compaction levels. The results are compared in terms of force-compaction-curves and occurring phenomena during compaction. The change of the material structure is characterized by sliding phenomena and crack initiation and growth.
Keywords: Polymers and Plastics; General Chemistry

A Data Driven Modelling Approach for the Strain Rate Dependent 3D Shear Deformation and Failure of Thermoplastic Fibre Reinforced Composites: Experimental Characterisation and Deriving Modelling Parameters - Gerritzen, Johannes; Hornig, Andreas; Gröger, Benjamin; Gude, Maik (Journal of Composites Science)
The 3D shear deformation and failure behaviour of a glass fibre reinforced polypropylene in a shear strain rate range of γ˙=2.2×10−4 to 3.4 1s is investigated. An Iosipescu testing setup on a servo-hydraulic high speed testing unit is used to experimentally characterise the in-plane and out-of-plane behaviour utilising three specimen configurations (12-, 13- and 31-direction). The experimental procedure as well as the testing results are presented and discussed. The measured shear stress–shear strain relations indicate a highly nonlinear behaviour and a distinct rate dependency. Two methods are investigated to derive according material characteristics: a classical engineering approach based on moduli and strengths and a data driven approach based on the curve progression. In all cases a Johnson–Cook based formulation is used to describe rate dependency. The analysis methodologies as well as the derived model parameters are described and discussed in detail. It is shown that a phenomenologically enhanced regression can be used to obtain material characteristics for a generalising constitutive model based on the data driven approach.
Keywords: Engineering (miscellaneous); Ceramics and Composites

Long-Term Behavior of Clinched Electrical Contacts - Kalich, Jan; Matzke, Marcus; Pfeiffer, Wolfgang; Schlegel, Stephan; Kornhuber, Ludwig; Füssel, Uwe (Metals)
Joining by forming operations presents powerful and complex joining techniques. Clinching is a well-known joining process for use in sheet metalworking. Currently, clinched joints are focusing on mechanically enhanced connections. Additionally, the demand for integrating electrical requirements to transmit electrical currents will be increased in the future. This integration is particularly important, for instance, in the e-mobility sector. It enables connecting battery cells with electrical joints of aluminum and copper. Systematic use of the process-specific advantages of this joining method opens up the possibility to find and create electrically optimized connections. The optimization for the transmission of electrical currents will be demonstrated for clinched joints by adapting the tool geometry and the clinched joint design. Based on a comparison of the electrical joint resistance, the limit use temperature is defined for the joining materials used based on the microstructural condition and the aging condition due to artificial aging. As a result of the investigations carried out, reliable current transmission at a constant conductor temperature of up to 120 °C can be achieved for clinched copper–copper joints. In the case of pure aluminum joints and mixed joints of aluminum and copper, long-term stable current transmission can be ensured up to a conductor temperature of 100 °C.
Keywords: General Materials Science; Metals and Alloys

Modelling and Simulation Strategies for Fluid–Structure-Interactions of Highly Viscous Thermoplastic Melt and Single Fibres—A Numerical Study - Gröger, Benjamin; Wang, Jingjing; Bätzel, Tim; Hornig, Andreas; Gude, Maik (Materials)
A virtual test setup for investigating single fibres in a transverse shear flow based on a parallel-plate rheometer is presented. The investigations are carried out to verify a numerical representation of the fluid–structure interaction (FSI), where Arbitrary Lagrangian–Eulerian (ALE) and computational fluid dynamics (CFD) methods are used and evaluated. Both are suitable to simulate flexible solid structures in a transverse shear flow. Comparative investigations with different model setups and increasing complexity are presented. It is shown, that the CFD method with an interface-based coupling approach is not capable of handling small fibre diameters in comparison to large fluid domains due to mesh dependencies at the interface definitions. The ALE method is more suited for this task since fibres are embedded without any mesh restrictions. Element types beam, solid, and discrete are considered for fibre modelling. It is shown that the beam formulation for ALE and 3D solid elements for the CFD method are the preferred options.
Keywords: General Materials Science

Electrical Contacting of Aluminum Bus Bars Using Clinching and Functional Elements - Füssel, Uwe; Schlegel, Stephan; Reschke, Gregor; Kalich, Jan (SFU/ICAFT 2022)
As a joining-by-forming process, clinching and the use of functional elements enable low-energy joining of components through form, force, and, under certain conditions, material closure. In addition to the transmission of mechanical forces, these joining processes can be qualified for additional electrical contact within the scope of functional integration for electro-mobile applications. For this purpose, maximizing the force and material closure is necessary to ensure a long-term, stable transmission of electrical currents. To this end, the electrical properties of the joints were optimized. The investigations carried out show the long-term behavior under normal operating conditions and the short-circuit case.

Influence of heat treatment on the suitability for clinching of the aluminium casting alloy AlSi9 - Neuser, Moritz; Böhnke, Max; Grydin, Olexandr; Bobbert, Mathias; Schaper, Mirko; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
In many manufacturing areas, multi-material designs are implemented in which individual components are joined together to form complex structures with numerous joints. For example, in the automotive sector, cast components are used at the junctions of the body and joined with different types of sheet metal and extruded profiles. To be able to join structures consisting of different materials, alternative joining technologies have emerged in recent years. This includes clinching, which allows assembling of two or more thin sheet metal and casting parts by solely cold forming the material. Clinching the brittle and usually less ductile cast aluminium alloys remains a challenge because the brittle character of the cast aluminium alloys can cause cracks during the forming of the clinched joint. In this study, the influence of the heat treatment time of an aluminium casting alloy AlSi9 on the joinability in the clinching process is investigated. Specific heat treatment of the naturally hard AlSi9 leads to a modification of the eutectic microstructure, which can increase ductility. Based on this, it will be examined if specific clinching die geometries can be used, which achieve an optimized geometrical formation of the clinched joint. The load-bearing capacities of the clinched joints are determined and compared by shear tensile and head tensile tests. Furthermore, the joints are examined microscopically to investigate the influence of the heat treatment on the failure behaviour during the load-bearing tests as well as crack initiation within the joining process.
Keywords: Mechanical Engineering; General Materials Science

Influence of solidification rates and heat treatment on the mechanical performance and joinability of the cast aluminium alloy AlSi10Mg - Neuser, Moritz; Grydin, Olexandr; Frolov, Y.; Schaper, Mirko (Production Engineering)
In modern vehicle chassis, multi-material design is implemented to apply the appropriate material for each functionality. In spaceframe technology, both sheet metal and continuous cast are joined to castings at the nodal points of the chassis. Since resistance spot welding is not an option when different materials are joined, research is focusing on mechanical joining methods for multi-material designs. To reduce weight and achieve the required strength, hardenable cast aluminium alloys of the AlSi-system are widely used. Thus, 85–90% of aluminium castings in the automotive industry are comprised of the AlSi-system. Due to the limited weldability, mechanical joining is a suitable process. For this application, various optimisation strategies are required to produce a crack-free joint, as the brittle character of the AlSi alloy poses a challenge. Thus, adapted castings with appropriate ductility are needed. Hence, in this study, the age-hardenable cast aluminium alloy AlSi10Mg is investigated regarding the correlation of the different thicknesses, the microstructural characteristics as well as the resulting mechanical properties. A variation of the thicknesses leads to different solidification rates, which in turn affect the microstructure formation and are decisive for the mechanical properties of the casting as well as the joinability. For the investigation, plates with thicknesses from 2.0 to 4.0 mm, each differing by 0.5 mm, are produced via sand casting. Hence, the overall aim is to evaluate the joinability of AlSi10Mg and derive conclusions concerning the microstructure and mechanical properties.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering